2005
DOI: 10.1007/s11881-005-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ literacy-related knowledge and self-perceptions in relation to preparation and experience

Abstract: After rating their own literacy-related knowledge in three areas (knowledge about reading/reading development, phonemic awareness/phonics, and morpheme awareness/structural analysis), graduate teacher-education students completed five tasks intended to measure their actual disciplinary knowledge in these areas. Teachers with high levels of prior background (i.e., course preparation and experience) rated themselves as significantly more knowledgeable than did low-background teachers in all areas; high-backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 16 publications
6
57
5
2
Order By: Relevance
“…Teacher educators in certain research settings exhibit sometimes-deficient knowledge about linguistic constructs, which is referred to as the 'Peter Effect' in the literature (Malatesha Joshi, Binks, Hougen, Dahlgren, OckerDean, & Smith, 2009;Binks-Cantrell, Washburn, Joshi, & Hougen, 2012). Many teachers in the field and in training are also inadequately prepared and perform below minimum standards (Spear-Swerling, Brucker & Alfano, 2005) revealing a lack of understanding concerning the basic language constructs needed to teach reading (Bos, Mather, Dickson, Podhajski & Chard, 2001;Moats, 1994;. While empirical research to date suggests a general association between teacher knowledge, teacher practice and student reading growth (Moats & Foorman, 2003), only a small number of studies have linked thus far the specific relationship between these constructs (McCutchen, Abbott, Green, Beretva, Cox, Potter, & Gray, 2002;McCutchen, Green, Abbott & Sanders, 2009;Podhajski, Mather, Nathan, & Sammons, 2009) so to characterize, inform and advance teacher education preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher educators in certain research settings exhibit sometimes-deficient knowledge about linguistic constructs, which is referred to as the 'Peter Effect' in the literature (Malatesha Joshi, Binks, Hougen, Dahlgren, OckerDean, & Smith, 2009;Binks-Cantrell, Washburn, Joshi, & Hougen, 2012). Many teachers in the field and in training are also inadequately prepared and perform below minimum standards (Spear-Swerling, Brucker & Alfano, 2005) revealing a lack of understanding concerning the basic language constructs needed to teach reading (Bos, Mather, Dickson, Podhajski & Chard, 2001;Moats, 1994;. While empirical research to date suggests a general association between teacher knowledge, teacher practice and student reading growth (Moats & Foorman, 2003), only a small number of studies have linked thus far the specific relationship between these constructs (McCutchen, Abbott, Green, Beretva, Cox, Potter, & Gray, 2002;McCutchen, Green, Abbott & Sanders, 2009;Podhajski, Mather, Nathan, & Sammons, 2009) so to characterize, inform and advance teacher education preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…Davis and Simmt 2006;De Nobile 2007;Spear-Swerling, Brucker and Alfano 2005). The emphasis on the teachers' subject theoretical knowledge, as a prerequisite for the profession, is noticeable when it comes to recruiting students with disciplinary skills to the teaching profession and making those teachers with disciplinary skills stay in the profession.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the last ten years, several studies in the area of reading instruction have examined teachers' disciplinary knowledge and teachers' perceived knowledge (e.g., Spear-Swerling, Brucker, & Alfano, 2005;Walsh et al, 2006). Cunningham et al (2004) found that their subjects were able to accurately calibrate their knowledge in the area of children's literature but not in the domains of phoneme awareness and phonics.…”
Section: Introductionmentioning
confidence: 99%